2009
DOI: 10.1136/jnnp.2008.168484
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac neurotransmission imaging with 123I-meta-iodobenzylguanidine in postural tachycardia syndrome

Abstract: Abstract:Background: Postural orthostatic tachycardia syndrome (POTS) is a disorder of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
14
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
4
14
0
2
Order By: Relevance
“…In this study,11 the investigators found reduced cardiac MIBG accumulation in four of 20 patients with POTS. They propose that this finding implies cardiac denervation.…”
supporting
confidence: 48%
See 1 more Smart Citation
“…In this study,11 the investigators found reduced cardiac MIBG accumulation in four of 20 patients with POTS. They propose that this finding implies cardiac denervation.…”
supporting
confidence: 48%
“…In this issue, Haensch and colleagues11 use the radionuclide 123 I-MIBG ( 123 I-meta-idobenzylguanidine) to study the neuronal uptake of norepinephrine (NE) in 20 patients with well characterised POTS ( see page ). The focus of this scintigraphic study is the synaptic junction; it utilises 123 I-MIBG as a substrate and false neurotransmitter that shares characteristics (uptake, storage and release) with NE, the major neurotransmitter of the sympathetic nervous system.…”
mentioning
confidence: 99%
“…8,16 Reduced myocardial meta-iodobenzylguanidine uptake has been reported in patients with POTS. 19 However, the relationship between this finding and peripheral adrenergic denervation of the lower limb is still undetermined. The frequent onset after a viral illness and the presence of a ganglionic acetylcholine receptor antibody in 14% of patients suggest an auto-…”
Section: Pots As a Syndrome Of Orthostatic Intolerancementioning
confidence: 99%
“…36 A recently published study reported that POTS might be a manifestation of autonomic cardiac neuropathy. 37 POTS has been reported associated with trauma, 38 Lyme disease, 39 electrocution, 40 multiple sclerosis, 41 and mitochondrial cytopathy 42 and also after ablation of slow pathway for atrioventricular (AV) node reentrant tachycardia. 43 Breath-holding spells The breath-holding spells group of disorders is usually seen in children and are broadly subdivided into 2 groups.…”
Section: Dysautonomic Syncopementioning
confidence: 99%